Disparate Intent-to-Treat Outcomes for Pediatric Liver Transplantation Based on Indication - Anna Lang; Cameron Goff; Ashley Montgomery; Jake Lynn; Spoorthi Kamepalli; John Goss; Abbas Rana (Canadian Journal of Gastroenterology and Hepatology)
Background. The impact of indication for pediatric liver transplantation on waitlist and post-transplant mortality outcomes is well known, but the impact on intent-to-treat outcomes has not been investigated. Intent-to-treat survival analysis is important in this study because it is more comprehensive, combining the transplant outcomes of waitlist mortality, post-transplant mortality, and transplant rate into a single metric to elucidate any disparities in outcomes based on indication. Methods. Cox regression was used to analyze factors impacting survival in 8,002 children listed for liver transplant in the UNOS database between 2006 and 2016. The Kaplan–Meier method and log-rank test were used to assess differences in waitlist, post-transplant, and intent-to-treat mortality among the top 5 indications of biliary atresia, acute hepatic necrosis, metabolic disorders, hepatoblastoma, and autoimmune cirrhosis. Results. When compared to the reference group of biliary atresia, multivariate analyses showed that every indication was associated with inferior intent-to-treat outcomes except for metabolic disorders. Hepatoblastoma (hazard ratio (HR): 3.73), autoimmune cirrhosis (HR: 1.86), and AHN (HR: 1.77) were associated with significantly increased intent-to-treat mortality. Hepatoblastoma was also associated with increased post-transplant mortality (HR: 3.77) and was the only indication significantly associated with increased waitlist mortality (HR: 6.43). Conclusion. Significant disparity exists across all indications with respect to an increased intent-to-treat mortality, along with an increased post-transplant and waitlist mortality, when compared to the biliary atresia reference group. If further studies validate these findings, a reexamination of the equitable distribution of allografts for transplant may be warranted as well as a focus on disparities in survival after transplant.